Neurocognitive Decrements are Present in Intellectually Superior Schizophrenia - Vaskinn, Anja; Ueland, Torill; Melle, Ingrid; Agartz, Ingrid; Andreassen, Ole A.; Sundet, Kjetil (Frontiers in Psychiatry, 2014)
Data suggests that individuals with schizophrenia (SZ) and superior intelligence can present without specific neurocognitive deficits. However, neurocognitive decrements, defined as worse cognition than expected, have been reported in practically all schizophrenia cases. This study investigated if neurocognitive decrements are present in intellectually superior SZ by comparing the neuropsychological profile of SZ cases with IQ-matched healthy controls (HC) across intellectual level. Participants with SZ and HCs were stratified into three IQ-groups; intellectually low (IQ 80-95; SZ n = 65 & HC n = 13), intellectually normal (IQ = 100-115; SZ n = 111 & HC n = 115) and intellectually superior (IQ > 120; SZ n = 20 & HC n = 50). A repeated measures multivariate analysis of co-variance compared performance on eight selected neuropsychological tests across IQ-strata and diagnostic group. Differences in clinical characteristics and social functioning in SZ across IQ-strata were investigated with multivariate and univariate analyses of variance. Intellectually superior SZ participants scored within normal limits, but had neurocognitive decrements compared to superior HCs. Decrements were of the same magnitude as in the low and normal IQ-strata. Levels of functional impairments and clinical characteristics in participants with SZ did not differ significantly across IQ-strata. Results indicate that neurocognitive decrements are present in intellectually superior SZ to the same extent as in intellectually low and intellectually normal SZ, supporting the notion that SZ is a neurocognitive disorder. Similar levels of social functional deficits and clinical symptoms suggest similar disease processes in SZ across intellectual level.